Actividades lúdicas que estimulen el desarrollo integral de niños y niñas en la etapa preescolar. - Orellana Medina, Cecilia María (2018)
In the processes of teaching and learning in the preschool contexts it is of vital importance to the implementation of recreational activities that stimulate the integral development of boys and girls in the formation stage due to the plasticity that have the same at this age. The current education seeks to integrate theoretical constructs, practical, emotional, psychological, social and family members in their educational curricula to convert the teaching in a dynamic element and not in a shirt of forces, in addition to the pedagogy plays a fundamental role in the process of training at all educational spaces has a purpose with the individual, being the main protagonist the teacher as facilitator of knowledge. In this sense, the didactics is the action of teaching using the resources necessary for the child to develop and learn. In addition, it is important to formulate that this science is to achieve the comprehensive training of the student. In this sense in this research is to identify activities that stimulate the integral development of boys and girls in the preschool stage. It is important to highlight that the Ecuadorian education system has gone through a number of political changes that have achieved key curricular processes to strengthen the teaching contents framed in the inclusion of innovative proposals. However, the educational system has much room for improvement in infrastructure, better remuneration, training, selection of professionals and technology.